Entrepreneurial opportunities : economics and sustainability for future growth - Ratten, Vanessa (Emerald Publishing Limited, 2020)
Focusing on sustainable innovation in emerging economies, this book is amongst the first to identify how these perspectives can be used by entrepreneurs within the process of recognising opportunities. As identifying opportunities is fundamental to successful entrepreneurship, it is crucial for aspirant entrepreneurs to identify appropriate openings that help them gain a competitive advantage in the international marketplace. Whilst there are an abundance of opportunities available, assessing them in terms of their timeliness and relevance is vital. Each chapter introduces a new way of looking at entrepreneurial opportunities in a range of different contexts including emerging markets, franchise relationships, pricing and revenue management, and the tourism sector. This global, cross-disciplinary perspective of entrepreneurial opportunities offers a unique blending of multiple theoretical viewpoints which are useful for researchers of entrepreneurship and entrepreneurs themselves. Enabling the development of both a social and financial view of entrepreneurship, Vanessa Ratten curates a collection which characterises and responds to the contemporary market pressures felt by business leaders worldwide.
Includes index.
Keywords: Entrepreneurship.; Economic development.; Business & Economics -- Entrepreneurship.; elektronické knihy; electronic books